PENGARUH IKLAN, PROMOSI PENJUALAN, DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP MINAT MEMAKAI ULANG LAYANAN GO-PAY DI WILAYAH JAKARTA - Priskilia Priskilia; Tony Sitinjak (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
One of the phenomena that occur in Indonesia in today’s era of globalization is Indonesian people who have used electronic wallet as electronic payment systems. This study aims to find out and get an idea of the influence of advertising, sales promotion, and perceived ease of use toward intention to reuse GO-PAY services in the Jakarta area. In this study, data were collected using communication study, namely by distributing online questionnaires through social media to 120 respondents who have used GO-PAY services in Jakarta. The sampling technique used is judgment sampling, where the sample took based on certain criteria or considerations. The selected criteria are people who have used GOPAY services in the Jakarta area. Data analysis was performed using multiple regression analysis techniques. The results of the research showed that advertising, sales promotion, and perceived ease of use had a positive effect on reuse intention. The research concludesthat advertising, sales promotion, and perceived ease of use had a positive influence on intention to reuse GO-PAY services.